1984
DOI: 10.1007/bf03214677
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion to gold: A review

Abstract: Asulab S.A., Passage Max-meuron 6, CH-2001 Neuchatel, Switzerland The adhesion ofsubstances to gold,, and our understanding ofit, is ofpotentialindustrial importance in a number of diverse fields such as heat transfer surfaces and jewelleiy manufacture.Adhesion is a complex subject and is not fully understood as yet. This explains the many different approaches followed in the field. For instance, in physics we calculate the ideal strength (1) and from a mechanics approach the force of adherence (2), while p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
14
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 22 publications
(11 reference statements)
5
14
0
Order By: Relevance
“…It is known, from studies of their wettability by liquids, that the energy of gold surfaces exposed to the atmosphere is low (1). The present study has revealed that this characteristic of gold surfaces is not materially affected if they are in contact with a polyurethane elastomer.…”
Section: Resultsmentioning
confidence: 48%
See 1 more Smart Citation
“…It is known, from studies of their wettability by liquids, that the energy of gold surfaces exposed to the atmosphere is low (1). The present study has revealed that this characteristic of gold surfaces is not materially affected if they are in contact with a polyurethane elastomer.…”
Section: Resultsmentioning
confidence: 48%
“…In a recent review article published in this journal (1), it was shown that gold has a low surface energy, involving essentially dispersive, rather than polar, interactions. This low surface energy could not be increased in spite of a variety of cleaning methods being used.…”
mentioning
confidence: 99%
“…The results indicate that droplet size has no effect on the equilibrium contact angles when spreading on the smooth substrates. The results of the equilibrium contact angles are comparable with those reported by Cognard (1984). In addition, it shows that there is no difference in the equilibrium contact angles on the substrates with different coating thicknesses.…”
Section: Spreading On Smooth Substratessupporting
confidence: 87%
“…For clean Au and Pt surfaces, the room temperature contact angle (θCA) at atmospheric pressure is in a range of 5-40°. [61][62][63][64][65] While, θCA of multilayer WS2 at RT is around 50-80°. 66,67 Also, in these works, the solid surface is more uniform and are in form of nanoparticle, and are smoother compared with the WS2 samples used in our experiment.…”
Section: Discussionmentioning
confidence: 99%